Investment in the infrastructure for hydrogen passenger cars – New hype or reality? - Bento, N. (Compendium of Hydrogen Energy: Hydrogen Storage, Distribution and Infrastructure focuses on the storage and transmission of hydrogen, 2015)
Hydrogen fuel cell vehicles have the potential to address both the environmental and oil dependency problems in transportation, but the construction of an infrastructure is a major issue that remains to be solved. This chapter reviews the challenges raised by the investment in infrastructure after the previous “hype” about hydrogen. The chapter analyzes the main obstacles posed by the establishment of a network of refueling stations and examines the strategies that have been followed by countries to deal with these barriers; in particular, in California, Japan, and Germany, where experience has shown how important cooperation is between actors (e.g., automakers, fuel suppliers, technology providers), as well as the support from public authorities to the installation of the early infrastructures. This analysis unveils not only the characteristics of the “revival” of an innovation after the disappointment, but also the strategies that have been followed to again gain visibility and come back to create the car of the future.